Association Between Dental and Oral Health Service Quality and Patient Satisfaction at Pakuan Baru Primary Health Care Center in Jambi, Indonesia - Septian Primalasari; Dwi Noerjoedianto; Willia Novita Eka Rini; Ummi Kalsum; Asparian (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Patient satisfaction is a key indicator of healthcare service quality, influencing trust and loyalty. The SERVQUAL model assesses service quality through five dimensions: tangible, reliability, responsiveness, assurance, and empathy. Objective: This study aimed to examine the relationship between service quality dimensions and patient satisfaction in dental health services. Method: A cross-sectional study was conducted at Pakuan Baru Public Health Center, Jambi City, from April 2025 to March 2026. A total of 190 respondents were selected from 341 patients using systematic random sampling. Data were collected through structured questionnaires and analyzed using chi-square tests and multiple logistic regression. Ethical approval was obtained (No. 1159/UN21.8/PT.01.04/2025). Results and Discussion: Overall, 51.58% of patients were satisfied. Significant associations were found between tangible (POR=7.37), reliability (POR=2.87), assurance (POR=4.76), and empathy (POR=5.87) and patient satisfaction (p<0.05). Multivariate analysis identified empathy as the most dominant factor (aOR=12.08; 95% CI=3.48–42.01). Conclusion: Service quality dimensions significantly influence patient satisfaction, with empathy as the strongest predictor. Improving interpersonal communication and healthcare facilities is essential to enhance patient satisfaction